Smart Finance: Desain dan Implementasi Sistem Keuangan Cerdas Real-Time Berbasis IoT untuk UMKM - Bendra Wardana; Pretty Naomi Sitompul (Politeknik Harapan Bersama, 2026)
The development of Internet of Things (IoT) technology and real-time data analytics provides opportunities to improve financial management efficiency for Micro, Small, and Medium Enterprises (MSMEs). However, most MSMEs in Indonesia still rely on manual bookkeeping, which is inefficient, prone to errors, and limits access to formal financing. This study aims to design and implement Smart Finance, an IoT-based intelligent financial system capable of processing transaction data automatically in real time. The research method includes system requirement identification, system design and device integration, application implementation, and system performance testing. The system was developed as a web-based application integrated with IoT devices such as ESP32-CAM to support automatic transaction recording, cash flow visualization, and digital financial report generation. The testing results indicate that the system can automatically record transactions with good accuracy, provide real-time financial dashboards, and deliver transaction notifications, thereby helping MSME owners monitor their financial conditions more quickly and transparently. The main contribution of this study lies in integrating IoT devices with a web-based financial recording system that enables automatic and real-time transaction recording, an approach that is still rarely implemented in MSME financial management. Although challenges related to internet connection stability remain, the developed system demonstrates potential in improving efficiency, transparency, and the quality of financial decision-making among MSMEs. This study concludes that Smart Finance can serve as a practical and adaptive digital financial solution to support the sustainability and competitiveness of MSMEs in the digital era.